Value Relevant Adopsi IFRS; Bukti Empris dari Seluruh Dunia - Andi Wawo (SEIKO : Journal of Management & Business, 2021)
Abstract This paper to provide a brief literatur and present empirical findings. The article covered 36 empirical papers published between 2008 and 2019 from various countries across continents. The research, we devided into 4 major groups based on continents namely Africa, Europe, Asia and Autralia as well as Latin America and Canada. The majority of them concluded that accounting information is more relevant across continents after IFRS adoption, while few hold the opposite view. Few studies show no evidence in the improvement of accounting information after IFRS adoption. Key Word; Adoption IFRS, Value Relevance